2006
DOI: 10.1111/j.1469-1809.2006.00280.x
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and Expression of C‐Reactive Protein in Type 2 Diabetes in the Diabetes Heart Study

Abstract: SummaryElevated C-reactive protein (CRP) levels are associated with both prevalent and incident cardiovascular disease. In this study, familial aggregation was estimated, and we tested for association between serum CRP levels and polymorphisms within the CRP and APOE genes in sib-ships with type 2 diabetes mellitus, a population at increased risk for cardiovascular disease. CRP levels were determined in 461 diabetes-affected subjects from 224 sibships from the Diabetes Heart Study (DHS). Heritability estimates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 25 publications
5
26
0
1
Order By: Relevance
“…The association between the common polymorphisms of APOE gene and the hs-CRP concentration was already reported in the elderly, 18,19 in dyslipidemic adults, 22 in type II diabetes 24 and in families. 12 However, there is no data about association between the APOE genotype and Table A1 in online appendix.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The association between the common polymorphisms of APOE gene and the hs-CRP concentration was already reported in the elderly, 18,19 in dyslipidemic adults, 22 in type II diabetes 24 and in families. 12 However, there is no data about association between the APOE genotype and Table A1 in online appendix.…”
Section: Discussionmentioning
confidence: 72%
“…16,17 Moreover, some other gene polymorphisms were associated with circulating levels of the hs-CRP, the most studied being the common polymorphisms of the apolipoprotein E gene (APOE) (e2, e3, e4) for which an association was confirmed by many authors in adults and elderly. 12,[18][19][20][21][22][23][24] However, no data exist either about APOE genotype-hs-CRP concentration association in children or about effect of these polymorphisms in combination with estimate of heritability component. 12 Thus, in the present analysis, we aimed at reporting on (i) the association between the APOE gene alleles with the serum hs-CRP concentration in adults and also in children, (ii) the familial aggregation of the serum hs-CRP concentration on a sample of French nuclear families and on (iii) the variance-component genetic linkage of this inflammatory factor with the alleles of the APOE gene.…”
Section: Introductionmentioning
confidence: 99%
“…This has indeed been hinted at in existing regression-based analyses where the partial r 2 for associated CRP polymorphisms has been <3% (Crawford et al, 2006;Kathiresan et al, 2006;Lange et al, 2006b). Of potential trans-acting influences, variation at the acute-phase cytokine genes interleukin-1β (IL1B) and interleukin-6 (IL6) and also apolipoprotein E (APOE) has been associated with basal CRP, albeit inconsistently (Berger et al, 2002;Chasman et al, 2006;Eklund et al, 2005;Judson et al, 2004;Lange et al, 2006a;Latkovskis et al, 2004;Marz et al, 2004;Paik et al, 2007;Shin et al, 2007;Vickers et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that genetic factors are likely to play a role in the inflammatory response in African Americans (24,25). Genes encoding critical proinflammatory cytokines, such as interleukin-1 and -6 and tumor necrosis factor-␣, have important roles in inflammatory diseases (24).…”
Section: Racial Disparities In Inflammation Markersmentioning
confidence: 99%